Validation of warfarin enantiomer analysis method in plasma using high-performance liquid chromatography fluorescence detector - Norisca Aliza Putriana; Taofik Rusdiana; Tina Rostinawati; Mohammad Rizki Akbar; Febrina Amelia Saputri; Siti Utami (Wolters Kluwer Medknow Publications, 2022)
Warfarin (WF) is an anticoagulant commonly used for thromboembolism-related diseases.This study aims to assess the pharmacokinetic profile of WF. The stereospecific interaction of S-and R-WF requires quantification of the enantiomer to determine the pharmacokinetic profile. The analysis method of the enantiomers in plasma is developed using an HPLC fluorescence detector with a Chiralcel OD-RH column (4.6 mm × 150 mm i.d., 5 m) and a Chiralcel OD-RH guard column (4.0 mm × 10 mm, 5 m). The separation is conducted using isocratic with acetonitrile mobile phase: Phosphate buffer, pH 2.00 (40:60 v/v), column temperature 40°C, flow rate 1 mL/min, injection volume 50 L. WF is measured at an excitation wavelength of 310 nm and emission of 350 nm. This method results in limit of detection (LOD) values of 18.6 ng/mL and limit of quantitation (LOQ) of 62.01 ng/mL for R-WF and LOD values of 18.61 ng/mL and LOQ of 62.04 ng/mL for S-WF. The results showed a linearity in concentration between 100 and 2500 ng/mL with r2 = 0.9969 and r2 = 0.9991 for R-and S-WF. The validation requirements of selectivity, accuracy, and precision for within and between run with a value of <15% for % relative standard deviation and % diff were achieved. This method can be used in the sample measurement of WF pharmacokinetic studies.